Islam, Multikulturalisme, dan Pancasila: Harmoni dalam Keberagaman Indonesia - Saputra, Edy; Husnani, Husnani; Defriza, Rita; Salma, Zakiati; Iska, Syukri (FASTABIQ: JURNAL STUDI ISLAM, 2024)
This article aims to analyze the relationship between Islam, multiculturalism, and Pancasila within the Indonesian context. The primary focus of this research is how the integration of Islam Wasatiyah - which emphasizes moderation and tolerance - with Pancasila as the state ideology can maintain social harmony amid diversity. Using a critical analytical method, this study finds that the synergy between Islam Wasatiyah and Pancasila strengthens social cohesion and prevents polarization caused by radicalism and identity politics. Furthermore, multicultural education and interfaith dialogue are identified as strategic instruments in promoting tolerance and preserving social stability. The research recommends strengthening multicultural-based education and promoting the values of Islamic moderation to address the challenges of radicalism in Indonesia.